Phytoseiid mites (Acari: Phytoseiidae) found in soil and litter from Atibaia, State of São Paulo, Brazil, with description of two new species - Mineiro, Jeferson L. C.; Lofego, Antonio C.; Sato, Mario E. (Taylor & Francis Inc, 2012)
Ten species of phytoseiid mites were found in the litter and soil of a coffee plantation (Coffea arabica L., Rubiaceae) in the State of São Paulo, Brazil. Two new species of phytoseiid mite, Amblyseius atibaiensis sp. nov. and Amblyseius terricola sp. nov., are described, and Amblyseius waltersi Schicha is reported for the first time in Brazil.
Keywords: Acari; predatory mite; taxonomy; Amblyseius atibaiensis; Amblyseius terricola